Bayesian Depth-from-Defocus with Shading Constraints - Li, Chen; Su, Shuochen; Matsushita, Yasuyuku; Zhou, Kun; Lin, Steve (The IEEE Conference on Computer Vision and Pattern Recognition (CVPR), 2013, 2013)
We present a method that enhances the performance of depth-from-defocus (DFD) through the use of shading information. DFD suffers from important limitations namely coarse shape reconstruction and poor accuracy on textureless surfaces that can be overcome with the help of shading. We integrate both forms of data within a Bayesian framework that capitalizes on their relative strengths. Shading data, however, is challenging to recover accurately from surfaces that contain texture. To address this issue, we propose an iterative technique that utilizes depth information to improve shading estimation, which in turn is used to elevate depth estimation in the presence of textures. With this approach, we demonstrate improvements over existing DFD techniques, as well as effective shape reconstruction of textureless surfaces.